Stroke units in Italy: engaging the public in optimizing existing resources. (6th March 2014) - Baldereschi, M.; Di Carlo, A.; Vaccaro, C.; Toni, D.; Polizzi, B.; Inzitari, D.; ,
<x xml:space="preserve">Abstract</x> Background and purpose The lack of a wide implementation of stroke units (SU)s in Italy appears to accompany the underuse of the operating units. Community awareness of acute stroke care options may affect stroke resource use. Our aim was to determine the level of knowledge about SUs and tissue‐plasminogen activator (t‐PA) treatment amongst Italian adults and investigate its relationship to local stroke services implementation. Methods A nation‐based telephone survey was carried out in a sample of 1000 residents aged >18 years in May–June 2010. The questionnaire included close‐ended questions regarding knowledge of SUs and t‐PA treatment. Number and location of both SUs and t‐PA treatments were provided by a concurrent national hospital‐based survey. The prevalence and distribution of acute stroke care awareness in the community was examined and multivariate analyses were generated. Results Amongst the 1000 participants (474 men, mean age 48.8 ± 17.2), only 26.2% reported knowing about the availability of t‐PA treatment and only 15% were aware of the existence of SUs. Awareness of both SUs and t‐PA was significantly associated only with education. These associations remained significant in the multivariate analyses. The degree of stroke services implementation (in terms of SUs/inhabitant rates and number of t‐PA treatments) was not associated with SU and t‐PA awareness. Conclusions This is the first European study that explored public knowledge about t‐PA treatment and SUs. Italian adults proved insufficiently educated about SUs and t‐PA; there is no higher awareness in areas with a greater supply of stroke services. This might partially explain the underuse of Italian SUs.